EFEKTIVITAS TEKNIK PERMAINAN UNTUK MENINGKATKAN PENYESUAIAN DIRI PESERTA DIDIK SEKOLAH DASAR TARUNA BAKTI KOTA BANDUNG (Jurusan Bimbingan dan Konseling Islam, 2015)
The purpose for this research is to know the effectiveness of game techniques to improve self-adjustment among 4th Graders in Taruna Bakti Elementary School year 2014-2015. The method used was a quasi experiment using a pretest-posttest nonequivalent control group design with a quantitative approach. The population for this research consists of 103 students, which consists of 22 participants were selected to be samples of this research, in which 11 were chosen to be part of the experimental group and the other 11 were chosen to be part of the control group. The instrument used to analyze was in the form of a questionnaire which was adopted from Rosidah (2013) from the social adjustment theory according to Schneiders, measuring 5 aspects of self adjustment that is : (1) the ability to form a bond of friendship with friends at school; (2) the ability to have a respectable behavior before teachers, the principal, and other school staff; (3) active to participate in school activities; (4) behave respectably and able to receive regulations in school; (5) and to help the school achieve its goals. The data were the analyzed by using paired t-test on SPSS 17.0 for windows program. The result indicates that the game technique was effective to improve students’ self-adjustment. It is recommended for principals, tutors, counselors, as well as future researchers.